Mechanical transplanting of rice in India: status, technological gaps and future thrust - Guru, Prabhat Kumar; Chhuneja, N K; Dixit, A; Tiwari, P; Kumar, Anjani (ORYZA-An International Journal of Rice, 2018)
Traditional way of rice transplanting is labor intensive and involves drudgery. Mechanical rice transplanter is costeffective and operation friendly. It helps in maintaining soil physical properties and is considered to be better from crop management and productivity point of view. In spite of having an edge over the traditional transplanting, adoption rate of mechanical transplanters is low due to high initial investment and lack of knowledge in growing mat type nursery. Imparting technical knowledge, ensuring timely availability and encouraging custom hiring may be some of the practical solutions for increasing the rice area under mechanical transplanting. This review summarizes the problems associated with rice transplanting, technological gaps in adoption of mechanical transplanter and future research to make transplanter more user friendly.